Hydrogenated liquid natural rubber for compatibility enhancement of poly (lactic acid) and natural rubber blends - Mohamad Shahrul Fizree Idris,; Nurfarhana Mohd Mustaffarizan,; Siti Fairus M. Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Non-catalytic hydrogenation of liquid natural rubber (LNR) via thermal decomposition of 2,4,6-trimethylbenzenesulfonylhydrazide (MSH) is reported in this study. Parameter studies of the hydrogenation reaction were performed by utilizing the combination of response surface methodology and central composite rotatable design (RSM/CCRD). The effects of each variable and the interaction between two variables (i.e. the MSH:LNR weight ratio and reaction time) were studied. Statistical analysis showed that the reaction time had significantly affected the hydrogenation percentage. A reduced quadratic model equation with the coefficient of determination (R2) value of 0.9875 was developed. The optimized condition as predicted by the software was compared with the experimental data, which deviated in only 0.67, hence indicating that this model was reliable and able to predict the hydrogenation percentage accurately. Fourier-transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies were used to characterize the microstructure of LNR and hydrogenated liquid natural rubber (HLNR). HLNR was then used as compatibilizer to improve the miscibility of poly(lactic acid)/natural rubber blends. With an addition of 4% HLNR, the tensile strength and impact strength of the blends were slightly improved.